Propagation and dissipation of typhoon-induced surface waves along the Pearl River Estuary - Liang, Mingen; Zhu, Suijie; Qiu, Heyong; Jia, Liangwen (Frontiers in Marine Science, 2024)
The propagation and dissipation of typhoon-induced surface waves are vital to morphological evolution and related engineering within coastal and estuarine regions. An observation system was operated during Typhoon Higos and TELEMAC-TOMAWAC numerical modeling was performed for typhoons Hagubit, Hato and Higos along the central coast of Guangdong and the Pearl River Estuaries in China to explore variation in wave propagation and dissipation during typhoons. The results showed that the wind waves were dominant before typhoon landfall, and the intense wind wave dissipated rapidly during typhoon decay whereas it could stay longer within the estuarine regions. Landward wave propagation had a tendency to convert from convergence dominated to dissipation dominated with the morphological change, and tended to converge at the mouth bar region. Within the estuarine regions, the wave dissipated more rapidly at the prismatic estuary than at the bell-shaped bays due to the limited width and rapid contraction of outlet. Moreover, the track and scale of typhoon had critical effect on the generated wave field, and they dominated the intensity, propagation and dissipation of the overall wave field. Specifically, typhoon with broader scale and longer moving track within the coastal regions of Guangdong province enhanced the wind-wave interaction and induced a stronger and wider wave field, despite their typhoon intensities were comparable (i.e. Hagubit .vs. Hato). Furthermore, wave generated by compact and regular cyclone structure dissipated stronger along the moving track of typhoon (i.e.Hato and Higos). Except for the typhoon directly attacked the PRE, wave within the estuarine regions tended to be dissipated/converged when it located at the right/left side of the moving track of typhoon.